The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1242/dev.02767
|View full text |Cite
|
Sign up to set email alerts
|

SEL-2, theC. elegansneurobeachin/LRBA homolog, is a negative regulator oflin-12/Notchactivity and affects endosomal traffic in polarized epithelial cells

Abstract: The vulval precursor cells (VPCs) of Caenorhabditis elegans are polarized epithelial cells that adopt a precise pattern of fates through regulated activity of basolateral LET-23/EGF receptor and apical LIN-12/Notch. During VPC patterning, there is reciprocal modulation of endocytosis and trafficking of both LET-23 and LIN-12. We identified sel-2 as a negative regulator of lin-12/Notch activity in the VPCs, and found that SEL-2 is the homolog of two closely related human proteins, neurobeachin (also known as BC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 70 publications
2
51
0
Order By: Relevance
“…12 LRBA is a member of a gene family involved in vesicle trafficking, 29,30 and we found that LRBA regulates CTLA-4 turnover in endosomes ( Figure 1C). 12 LRBA helps maintain an intracellular vesicular pool of CTLA-4 for immediate mobilization to the cell surface as needed.…”
Section: Blood 25 August 2016 X Volume 128 Number 8 Chai and Lataiementioning
confidence: 74%
“…12 LRBA is a member of a gene family involved in vesicle trafficking, 29,30 and we found that LRBA regulates CTLA-4 turnover in endosomes ( Figure 1C). 12 LRBA helps maintain an intracellular vesicular pool of CTLA-4 for immediate mobilization to the cell surface as needed.…”
Section: Blood 25 August 2016 X Volume 128 Number 8 Chai and Lataiementioning
confidence: 74%
“…Most commonly, endocytosis followed by receptor degradation terminates signaling. However, endocytosis can also prolong the duration of signaling (Jullien and Gurdon, 2005) or influence its subcellular location (de Souza et al, 2007;Howe and Mobley, 2005). Receptors may also signal through different downstream pathways localized to specialized endosomal compartments (Di Guglielmo et al, 2003;Miaczynska et al, 2004;Teis et al, 2006).…”
Section: Endocytosis and Receptor Signalingmentioning
confidence: 99%
“…Bchs is a member of the Beige and Chediak-Higashi (BEACH) family of proteins whose role in vesicular trafficking has been described previously (Wang et al, 2000;Ward et al, 2000;Cornillon et al, 2002;Su et al, 2004;de Souza et al, 2007). The abnormal accumulation of ubiquitinated proteins in bchs brain tissue and the ability of lysosomal mutations to suppress a Bchs overexpression eye phenotype, suggested a possible role in degradation (Finley et al, 2003).…”
Section: Introductionmentioning
confidence: 96%